2012
DOI: 10.3892/or.2012.1785
|View full text |Cite
|
Sign up to set email alerts
|

Soluble E-cadherin and IL-6 serum levels in patients affected by prostate cancer before and after prostatectomy

Abstract: Abstract. Prostate specific antigen (PSA) is still the best available tumour marker in prostate cancer (PCa), but presents some limits. Therefore, there is a need for novel markers in the detection and management of PCa. The 80-kDa soluble form of E-cadherin (sE-cad) and the cytokine IL-6 are being discussed as supplemental serum markers for PCa. In this study, sE-cad and IL-6 serum levels were determined in patients with pathological localized or locally advanced PCa without any previous treatment. These pati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
3
0

Year Published

2012
2012
2015
2015

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 26 publications
(44 reference statements)
1
3
0
Order By: Relevance
“…Later, Kuefer et al [ 26 ] observed no difference between the expression of serum sE-cadherin in 61 men with localized PCa compared to controls. On the contrary, a more contemporary series also involving 61 patients with clinically localized PCa, reported by Iacopino et al [ 27 ], demonstrated serum sE-cadherin over-expression in PCa patients compared to that of healthy individuals, which is similar to our observation. However, no correlation of the marker with PSA, T-stage, GS, grade or R- and Pn-status was observed by those investigators.…”
Section: Discussionsupporting
confidence: 92%
“…Later, Kuefer et al [ 26 ] observed no difference between the expression of serum sE-cadherin in 61 men with localized PCa compared to controls. On the contrary, a more contemporary series also involving 61 patients with clinically localized PCa, reported by Iacopino et al [ 27 ], demonstrated serum sE-cadherin over-expression in PCa patients compared to that of healthy individuals, which is similar to our observation. However, no correlation of the marker with PSA, T-stage, GS, grade or R- and Pn-status was observed by those investigators.…”
Section: Discussionsupporting
confidence: 92%
“…IL-6 is known to be increased in patients with advanced stages of PCa (55, 56), play an important role in PCa progression (57), and can be secreted from several cell types, including macrophages (58) and adipocytes (59). In this study we found ECs are another source of IL-6.…”
Section: Discussionmentioning
confidence: 99%
“…Interleukin-6 (IL-6) is a pleiotropic cytokine that stimulates proliferation and modulates key cellular events in prostate cancer [ 1 ]. The expression of IL-6 is elevated in advanced prostate cancer [ 2 ] and correlates with the Gleason grade of prostate cancer [ 3 ] and prostate cancer progression [ 4 ]. IL-6 is a major activator of the Janus kinase/signal transducer and activator of transcription 3 pathway in prostate cancer [ 5 ].…”
Section: Introductionmentioning
confidence: 99%